2014
DOI: 10.4271/2014-01-2787
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Boundary Lubrication Performance of Engine Oils on Friction at Piston Ring-Cylinder Liner Interface

Abstract: To explore the measures that can be used to improve the fuel economy of internal combustion engines, we investigated how friction at the piston ring-cylinder liner interface is influenced by the boundary lubrication performance of engine oils. We formulated several engine oils with varying boundary lubrication performance and tested them for ring-liner friction by using a floating liner friction tester. We used friction modifiers (FMs) to modify the boundary lubrication performance of engine oils. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…The typical features of f c0 and f ch against h T demonstrated in Figs. 8(b) and (c) are similar to the measured results by Tamura et al [5] using a floating liner friction tester. They showed that engine oil with a friction modifier, particularly MoDTC additives, exhibited similar mixed lubrication and boundary lubrication friction.…”
Section: Load Capacity and Friction Coefficient When N = 3 Andsupporting
confidence: 88%
See 1 more Smart Citation
“…The typical features of f c0 and f ch against h T demonstrated in Figs. 8(b) and (c) are similar to the measured results by Tamura et al [5] using a floating liner friction tester. They showed that engine oil with a friction modifier, particularly MoDTC additives, exhibited similar mixed lubrication and boundary lubrication friction.…”
Section: Load Capacity and Friction Coefficient When N = 3 Andsupporting
confidence: 88%
“…Typical examples reported are the super-low friction coefficient in water-lubricated SiC-SiC sliders with micro-/nano-order textures after the running-in process [1,2] and the reduction of mixed lubrication friction and transition from boundary lubrication to hydrodynamic lubrication regime of the slider lubricated with alkyl acid phoshate additive oil after the running-in [3,4]. Hydrodynamic friction in reciprocating internal combustion engines was decreased by reducing the base oil viscosity, whereas severe friction at the dead center was mitigated by blending the base oil with additives such as MoDTC [5]. This low friction and high load capacity caused by enhanced viscosity in a surface layer have attracted much research attention from tribologists.…”
Section: Introductionmentioning
confidence: 99%
“…As a rule of thumb, upgrading the engine's lubricants can advance the fuel economy and the overall engine's system [163]. A valuable advantage of nanolubricants is their ability to bring down both the fuel consumption and the harmful exhaust emissions of engines.…”
Section: Fuel Economy and Emissionsmentioning
confidence: 99%
“…Other engine oils, including anti-wear additives and friction modifiers, showed rapid increases in viscosity (of more than 100 times) above a 180 nm film thickness. This significant increase in viscosity, with a decrease in film thickness from more than 100 nm, seems to contribute to fluid lubrication in the otherwise mixed lubrication regimes near dead-center positions, even when a low-viscosity base oil is used [6].…”
Section: Introductionmentioning
confidence: 97%